Data Driven Assistance for Improving the Quality of Integrated Primary Dental Health Services in Pringkasap Public Health Center, Subang Regency - Nina Narjati Soejoto; Irda Sari (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
Primary care performance at Puskesmas Pringkasap in 2025 did not meet the PKP-ILP target (>=80%), as reflected by low outpatient visit coverage and suboptimal completion of dental and oral health case management among the target population. This community service program aimed to strengthen PKP-ILP implementation through participatory, data-driven mentoring to improve the consistency of indicator monitoring and accelerate service gains. The program was conducted from January to December 2025 using a quarterly action cycle: (1) baseline review of quarterly achievement using NUM-DEN-HSL components; (2) a workshop to align indicator definitions, service flow, and documentation standards; (3) on-the-job coaching for outpatient and dental teams to improve target outreach and follow-up; and (4) quarterly audit-and-feedback sessions complemented by action plans and routine monitoring. Key barriers included inconsistent recording, variable adherence to follow-up procedures, and limited reach to target groups. Outpatient coverage improved from 9.39% (Q1) to 18.60% (Q4), with a cumulative achievement of 50.30% (10,558/20,990). Dental and oral health management remained stable at 38.02-39.54% per quarter. The mentoring process produced a concise SOP for indicator documentation, an agreed internal referral flow, and a routine data review mechanism involving program leads. In conclusion, PKP-ILP mentoring strengthened data governance and supported service improvement; however, additional demand-side strategies (health education, visit reminders, and community cadre collaboration) are needed to achieve the >=80% target.